Customer Relationship Management Systems Handbook - Sharp, Duane (CRC Press, 2009)
The concept of customer relationship management (CRM) has grown from the loosely defined methodology of using customer transactions for developing profiles on customers to the well-defined business process of using sophisticated tools and analytical processes for managing each customer on an individual basis. CRM integrates e-mail and the PDA with the day planner, electronic scheduler, client database, and a number of other business management tools so you can create a single point from which to manage customer relationships.